Criminological Review of Sexual Offenses Committed by Children - I Gede Wiarta; Dwi Ratna Kamala Sari Lukman; Wihelmus Jemarut; I Nyoman Suarna; I Nyoman Sumantri; I Gusti Agung Andriani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Crimes of sexual intercourse committed by children are one type of crime that requires special attention, especially as the incidence of such crimes committed by children has been increasing year by year. The significant impact resulting from this crime should certainly be a matter of our collective concern. Therefore, this research aims to identify the factors underlying why children commit sexual offenses and the rehabilitation efforts undertaken by the Special Child Development Institution Class II Lombok Tengah for children who commit sexual offenses. This research is empirical in nature. Data in this research were obtained using observation methods, interviews, documentation, and literature study. The data were then analyzed using a sociological approach, a case study approach, and a legislative approach. The data was then presented using a descriptive qualitative method. The research results show that the factors causing children to commit sexual offenses are poor environmental factors, social media factors, and lack of parental supervision. Meanwhile, the efforts made by the Special Child Development Institution Class II Lombok Tengah for children who commit sexual offenses are personality development, including spiritual development, national and state awareness, reintegration, and intellectual development, and independence development, including horticulture, agriculture, basic welding techniques, and barbershop skills.